Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Courtney, Travis A.; Andersson, Andreas J.; Bates, Nicholas R.; Collins, Andrew; Cyronak, Tyler; de Putron, Samantha J.; Eyre, Bradley D.; Garley, Rebecca; Hochberg, Eric J.; Johnson, Rodney; Musielewicz, Sylvia; Noyes, Tim J.; et al. (Frontiers in Marine Science, 2016)
Coral reef net ecosystem calcification (NEC) has decreased for many Caribbean reefs over recent decades primarily due to a combination of declining coral cover and changing benthic community composition. Chemistry-based approaches to calculate NEC utilize the drawdown of seawater total alkalinity (TA) combined with residence time to calculate an instantaneous measurement of NEC. Census-based approaches combine annual growth rates with benthic cover and reef structural complexity to estimate NEC occurring over annual timescales. Here, NEC was calculated for Hog Reef in Bermuda using both chemistry and census-based NEC techniques to compare the mass-balance generated by the two methods and identify the dominant biocalcifiers at Hog Reef. Our findings indicate close agreement between the annual 2011 census-based NEC 2.35±1.01 kg CaCO3•m-2•y-1 and the chemistry-based NEC 2.23±1.02 kg CaCO3•m-2•y-1 at Hog Reef. An additional record of Hog Reef TA data calculated from an autonomous CO2 mooring measuring pCO2 and modeled pHtotal every 3-hours highlights the dynamic temporal variability in coral reef NEC. This ability for chemistry-based NEC techniques to capture higher frequency variability in coral reef NEC allows the mechanisms driving NEC variability to be explored and tested. Just four coral species, Diploria labyrinthiformis, Pseudodiploria strigosa, Millepora alcicornis, and Orbicella franksi, were identified by the census-based NEC as contributing to 94±19% of the total calcium carbonate production at Hog Reef suggesting these species should be highlighted for conservation to preserve current calcium carbonate production rates at Hog Reef. As coral cover continues to decline globally, the agreement between these NEC estimates suggest that either method, but ideally both methods, may serve as a useful tool for coral reef managers and conservation scientists to monitor the maintenance of coral reef structure and ecosystem services.